Structure in language schools (concept, classification and trends) (Journal of Human Sciences, 2023)
Language is the focus of the study, its inexhaustible source, and the field of interest of the researcher who draws his ideas from it. Due to its smoothness, it is incapable of obsolescence, and the factor of time does not affect it. The issue of exposure to the study of the language as a unit of matrix elements, and the variety of sections, is difficult to achieve if it is related to the expansion of the boundaries of the structure of the language, and what it enjoys of morphological, phonetic, lexical, and grammatical characteristics. Conditions isolate language from its features. This article seeks to study the structure of language as a tool of communication and is rooted since ancient times with human origin and inherent to him. Language is characterized by flexibility and appears in the ability of its user to adapt it to achieve expressive purposes. This article also aims to study the reality of this concept in traditional schools. And linguistic schools, and seeks, on the other hand, to explain how the structure of the language has been treated by observing the changes that occur to it, and this is only possible if its structure is subjected to description and interpretation. to explain.